2020
DOI: 10.1051/parasite/2020020
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of resistance to satyrization behavior in Aedes aegypti from La Réunion island

Abstract: Aedes aegypti and Aedes albopictus are competent vectors of arboviruses such as dengue and chikungunya viruses which co-exist in some areas, including La Réunion island, Indian Ocean. A type of reproductive interference called satyrization has been described in sympatric species where dominant species mating fails to produce hybrids and thus reduces the fitness and tends to control the spread of the other species. Here, we investigated satyrization in laboratory experiments to provide insights on the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…aegypti females have autogenous activity [28] as observed in one cage of controls. Our results agree with those of Harper and Paulson [29] and Maiga et al [24] who demonstrated that the mating of Ae. aegypti and Ae.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…aegypti females have autogenous activity [28] as observed in one cage of controls. Our results agree with those of Harper and Paulson [29] and Maiga et al [24] who demonstrated that the mating of Ae. aegypti and Ae.…”
Section: Discussionsupporting
confidence: 94%
“…Although such a reduced egg hatch rate might presumably reflect the cost of satyrisation, no such changes were observed in our study. Consistent with a recent study reported by Maiga et al [24], this suggests that in our conditions, even if interspecies induction of refractory period occurred, it is very limited and has no impact on the final product of mating: the quantity of offspring. Despite this, in the context of SIT that involve the inundative release of sterile males to selectively control the target species, future research under natural conditions should aim at gaining a quantitative understanding of the potential impact of an increased heterospecific mating rate following sterile male release on the dynamics of coexisting Aedes species and subspecies (if any).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A feasibility assessment of an area-wide integrated pest management (AW-IPM) program with an SIT component against Ae. albopictus is also ongoing on La Réunion island [ 20 , 21 ] and in Mauritius [ 22 ]. Moreover, the invasion of Europe by this species has triggered the development of a vector control management plan [ 23 ], and several countries, including Albania, Greece, Germany, Montenegro, and Spain, have initiated pilot trial releases of sterile males against Ae.…”
Section: Introductionmentioning
confidence: 99%